Cytotoxicity, production of superoxide anion (O-2) and DNA fragmentation in murine macrophages by azodicarbonamide - Irving Jork Chang Espinoza (2019)
Azodycarbamide (ADA) was suggested as anti foaming agent or plastic expandeer for plastic in Germany in the fifties. Today it is one of the most used foaming agents. Another use of Azodycarbamideis in food industry for bread products where it is used as axydizing agent. In this study we have studied the toxicity of Azodycarbamide through reaction with Methyl—Tiazole Tetrazolium (MTT). Also, the reduction assay with NBT (Tetrazolium Nitro Blue) was used to determine the percenatage of production of superoxide anion . In these assays, murine macrophages of rats were incubated in RMPI-1640 medium with different concentrations of Azodycarbamide (3Oppm, 4Oppm y 5Oppm). On the other hand, a DNA electrophoresis was performed to determine DNA fragmentation.Our results showed that at similar concentratons to those used by MERCOSUR (4Oppm) and FAD(45ppm), there was evidence of cytotoxicity , associated to induction of superoxide anion and also DNA fragmentation. This is demonstration that Azodycarbamide in the cinditrons if this study is not totally innocuous . however, results obtained deserve further study